Exploring expected and perceived facilitators and barriers of an indicated prevention strategy to prevent future long-term sickness absence; a qualitative study among employers and employees - Sophie H. Klasen; Ludovic G. P. M. van Amelsvoort; Inge Houkes; Nicole W. H. Jansen; IJmert Kant (BMC, 2021)
Abstract Background An indicated prevention strategy (IPS), consisting of a screening questionnaire and early treatment, was found to be effective for the prevention of future long-term sickness absence (LTSA) in two large Dutch RCT's. This IPS aims to detect employees who have a high risk to become absent, and subsequently offer them early treatment. Despite the overall effectiveness, only a few companies have implemented this strategy so far. This suggests that companies may not be convinced of the (cost) effectiveness of this strategy yet. In companies where IPS has been implemented, screenings uptake and adherence to early treatment appeared to be moderate, indicating that both employees and employers might perceive barriers. Methods The aim of this qualitative study was to explore the expected and perceived facilitators and barriers for the implementation of the IPS. Semi-structured interviews were conducted with 9 employers and 11 employees (acquainted and unacquainted with IPS) from large companies. Purposive sampling was used to recruit participants. All interviews were transcribed and analyzed thematically. Results The employers believed they were primarily responsible for psychological and work-related health complaints and SA, while the employees felt responsible for health complaints related to their lifestyle. According to the employees, the responsibility of the employer was solely related to work-related health. This finding exposed a relation with the health culture, which was solely based on creating a safe work environment, omitting psychological health issues. The efficacy of this IPS regarding reducing SA was estimated positive, however, the efficacy regarding LTSA was questioned. Fear of a privacy breach was often mentioned by the respondents as an important barrier. Conclusions This study showed that the health culture within a company may be important for the perceived responsibility towards SA and health. A health culture which primarily focuses on physical complaints may raise barriers for the adoption and implementation of this preventive strategy. Participant' perceptions of the nature of LTSA and the fact that not all participants were familiar with the exact content and phasing of IPS may have doubted the efficacy regarding LTSA. This study provides important clues for future and improved implementation of IPS.